2018
DOI: 10.1016/j.vaccine.2018.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic and sequence variability of the human respiratory syncytial virus F glycoprotein compared to related viruses in a comprehensive dataset

Abstract: A comprehensive analysis of sequence variation was carried out comparing the fusion (F) protein of human respiratory syncytial viruses (hRSV) from antigenic groups A and B with the prototype sequence of the A2 strain, also belonging to antigenic group A. The limited number of full bovine RSV F sequences available were included, as well as an extensive set of F sequences from the related human metapneumovirus (hMPV). The results were analysed in the context of the recently determined three dimensional F protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 58 publications
6
49
0
Order By: Relevance
“…Outside this conserved patch, previous analysis of a large number of sequences revealed that site Ø of RSV F is the most variable site with divergent sequences. 54 A recent report of two new site Ø mAbs with different RSV A and B specificities also highlighted the structural variations of this antigenic site. 45 Among the isolated highly potent mAbs in this study, we indeed found that mAbs targeting site Ø showed the most variations in neutralization potencies between the two different RSV subtypes, including a strain A-specific mAb 139B8.…”
Section: Discussionmentioning
confidence: 97%
“…Outside this conserved patch, previous analysis of a large number of sequences revealed that site Ø of RSV F is the most variable site with divergent sequences. 54 A recent report of two new site Ø mAbs with different RSV A and B specificities also highlighted the structural variations of this antigenic site. 45 Among the isolated highly potent mAbs in this study, we indeed found that mAbs targeting site Ø showed the most variations in neutralization potencies between the two different RSV subtypes, including a strain A-specific mAb 139B8.…”
Section: Discussionmentioning
confidence: 97%
“…A study by A. Hause et al 22 compared the F sequences of over 1000 viral isolates found that site IV was highly conserved (>99%) across all genotypes. Furthermore, a study by V. Mas et al 23 found that sites III and IV were the most conserved regions of the protein. They further argued that pre- and post-F share secondary structural elements within sites III and IV and these constitute the inter-protomeric cavity of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Sites III and IV of the protein are conserved to some extent between RSV A, B, and the related virus HMPV; therefore, they may also be required for genetic stability. In contrast, placement of site Ø and V on the apex region may require structure flexibility resulting in less conserved sequences 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, there were 5 residues in the prefusion-specific site Ø with significant entropy (Figure 5B). This scarcity of sequence variation in most antigenic sites except site Ø has been observed in an analysis of RSV clinical isolates [70].…”
Section: Resultsmentioning
confidence: 96%